Hippasteria phrygiana Parelius 1768 - Mah, Christopher L. (Zenodo, 2016)
Hippasteria phrygiana (Parelius 1768) Mah et al. 2014: 441 (as H. phrygiana ) covers complete synonymy. Comments. Foltz et al. (2013) and Mah et al. (2014) have extensively examined the global phylogeography of this species and concluded that several Pacific Hippasteria species, including Hippasteria spinosa , which have been studied at SCUBA depths in the Northwest Pacific (e.g., Birkeland et a. 1974; Mauzey et al. 1968) were synonyms. Although Hippasteria phyrgiana has not been recorded from below 1000 m in the Pacific Northwest, it has apparently been collected from deeper depths elsewhere (e.g, Maluf 1987). Thus, it is possible that H. phrygiana could occur at deeper depths from the region covered herein. Alternatively it is also possible that there is morphological convergence as there was some morphological similarity between H. phrygiana and specimens of H. californica and H. tiburoni , all different species but showing very similar diagnostic features. Occurrence. (data taken from Mah et al. , 2014) North Pacific: Japan, Aleutian Islands, Alaska, west coast of North America, including Canada, Washington, Oregon, west to President Jackson Seamount, south to Southern California. South Pacific: New Zealand, Solomon Islands, Straits of Magellan-Chile. South Indian: Kerguelen Islands, Crozet, Marion and Bouvet Isles, South Africa. Atlantic: East coast of North America, south to Cape Cod. Northeastern Atlantic-North Sea, Kattegat, northern Scotland and northernmost Ireland, the UK. South Atlantic-off Argentina, west side of South Africa, Lambert’s Bay to Cape Point. 10–1405 m (but varies by location). Published as part of Mah, Christopher L., 2016, Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species, pp. 101-141 in Zootaxa 4175 (2) on page 117, DOI:10.11646/zootaxa.4175.2.1, http://zenodo.org/record/257286